(untitled) (Journal of Medical & Health Sciences Review, 2025)
One of the most frequent causes of doctor visits worldwide is gastroenteritis. Acute gastrointestinal disorders are a major medical and financial concern. Such conditions need to be managed more skillfully. There is still much to learn about how to lower the risk of intestinal infections through diet. Antibiotics can effectively inhibit infections, but they cannot be used prophylactically and should not be provided in the absence of sickness. Probiotics, or beneficial bacteria found in the gut, have been shown to have a variety of inhibitory effects on pathogens. Probiotics are currently gaining popularity due to the growing antibiotic resistance of pathogenic bacteria, especially in hospitals, as well as clinical data demonstrating the effectiveness of some probiotic bacteria. One probiotic that is good for human health is Bacillus clausii. One of its primary traits is the capacity to proliferate; the ensuing resistance to heat, acid, and salt guarantees an accessible route via the human digestive system without cellular loss. The advantageous qualities of other probiotics, like Lactobacillus and Bifidobacterium species, are more commonly known throught the literature, despite the fact that B. clausii has been utilized extensively for many years.